Keseimbangan Badan dan Jiwa Perspektif Abu Zaid Al-Balkhi - Musfihin Musfihin (Faculty of Ushuluddin and Humanities, 2019)
Abu Zaid al-Balkhi was a multi-talent scientist in 9th-century Islam in several fields, his ability to write two themes in a systematic work had brought him to be known as the first mental health pioneer who before that time prioritized physical health. The purpose of this study is to describe the concept of Body and Soul according to Abu Zaid al-Balkhi, using the Research Library method from the data of Abu Zaid al-Balkhi's work entitled